On Presented Dimensions of Modules and Rings - Dexu Zhou; Zhiwei Gong (International Journal of Mathematics and Mathematical Sciences)
We define the presented dimensions for modules and rings to measure how far away a module is from having an infinite finite presentation and develop ways to compute the projective dimension of a module with a finite presented dimension and the right global dimension of a ring. We also make a comparison of the right global dimension, the weak global dimension, and the presented dimension and divide rings into four classes according to these dimensions.